High performance silicon lateral PIN photodiode - Tasirin S.K.; Menon P.S.; Ahmad I.; Abdullah S.F. (Institute of Physics Publishing, 2023)
Start Photodetectors with high responsivity in Si-related processes are required for high speed optoelectronic applications such as fiber optic data communication systems. In this paper, the performance of a virtual lateral PIN photodiode with intensity response in the 200-1000 nm wavelength range was demonstrated. The results obtained for responsivity, total quantum efficiency and frequency response were 0.62 A/W and 13.1 GHz respectively for design parameters of intrinsic region length of 6 ?m, photoabsorption layer thickness of 50 ?m, incident optical power of 1 mW/cm2 and bias voltage of 3 V. As a conclusion, the decrease in device size enabled the realization of a high performance lateral p-i-n photodiode. Published under licence by IOP Publishing Ltd.